INTEGRATED MANAGEMENT CYBERNETICS AS A FOUNDATION FOR ORGANIZATIONAL RESILIENCE - Pieter BUYS (Studia Universitatis Babeș-Bolyai. Philosophia, 2021)
he 4th Industrial Revolution introduced a highly automated and connected business environment. Nevertheless, many organizations are reeling in the wake of the speed and severity of the COVID-19 pandemic's impact, catching many unawares, and placing their sustainability in question. Given the connectedness promulgated by the 4th Industrial Revolution, one might expect organizational resilience to be a given - only time will tell whether this was the case. This article considers the concept of cybernetics as contributing to systems-thinking, which may enable resilience strategies to come to fruition. Cybernetics is a goal-driven approach in which constant feedback is analyzed and applied in correcting the current course. We reflect on the roots and principles of the cybernetic concept, developing it into a management cybernetics concept. We take a non-technological approach in acknowledging organizations as systems. Management theories such as stakeholder and stewardship theories are systems components that can play a crucial role in effectively communicating management information within the cybernetic loop. We conclude that an integrative and cooperative relationship with legitimate stakeholders can play an essential role in an organization's preparedness.